1988
DOI: 10.1007/bf02400486
|View full text |Cite
|
Sign up to set email alerts
|

The study on supported Fe and FeMo hydrotreating catalysts by combining Mössbauer spectroscopy and ordinary γ-ray transmission

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Similar conclusions were obtained from research on alumina-supported TMS . Meanwhile, several research groups studied the promoter effect of Fe on the HDS activity of MoS 2 , , and a FeMoS phase, which has a structure similar to that of the CoMoS phase, was proposed to be responsible for the weak synergetic effect of the FeMo catalyst. Other combinations such as FeW, FeV, and FeNi were also explored; it was found that Fe could incorporate easily with the above secondary metals, leading to the formation of Fe x W y C/N and pentlandite species and improving the dispersion of V active sites.…”
Section: Introductionsupporting
confidence: 70%
“…Similar conclusions were obtained from research on alumina-supported TMS . Meanwhile, several research groups studied the promoter effect of Fe on the HDS activity of MoS 2 , , and a FeMoS phase, which has a structure similar to that of the CoMoS phase, was proposed to be responsible for the weak synergetic effect of the FeMo catalyst. Other combinations such as FeW, FeV, and FeNi were also explored; it was found that Fe could incorporate easily with the above secondary metals, leading to the formation of Fe x W y C/N and pentlandite species and improving the dispersion of V active sites.…”
Section: Introductionsupporting
confidence: 70%
“…Instead of Mo- and W-based catalysts, some scholars paid more attention to Fe-based catalysts due to the abundant reserve, low cost, and environmental sustainability. While others introduced Mo, Ni, or V onto the Fe-based catalyst to further improve the HDS activity, a synergistic effect between Fe and these metal species on the HDS process was observed. However, few studies focused on Fe-based catalysts, an active phase for the HDS process, due to their inherent low activity. Although it had been widely considered that the Fe-based catalysts exhibited poor HDS performance in the past few years, the addition of the Zn element would significantly enhance the HDS activity, which was reported in our previous study .…”
Section: Introductionmentioning
confidence: 99%